Argentina's Convertibility Plan and the IMF - Cavallo, Domingo; Cottani, Joaquin A. (American Economic Review, 1997)
Almost six years have passed since Argentina introduced a currency board system called convertibility. It consists of a one-for-one peg between the peso and the U.S. dollar and full backing of the monetary base with international reserves. In spite of its resounding success in reducing inflation, there is still a considerable degree of skepticism in the world, although not so much in Argentina, about whether convertibility is a suitable monetary arrangement for the long run. Prestigious economists have argued that convertibility was a useful tool to stop hyperinflation in Argentina but that it is not suitable for countries facing less dramatic conditions (see John Williamson [1995] and the speeches by Max Corden, Stanley Fischer, and Williamson in World Bank [1997]). According to them, even Argentina should think of abandoning this system as a way to promote economic growth and higher employment. International institutions like the International Monetary Fund and the World Bank have been extremely supportive of convertibility in Argentina. But in private they are concerned about what Sebastian Edwards, former World Bank chief economist for Latin America, has called the exit problem, (i.e., how a country like Argentina can get out of the commitment to a fixed exchange rate without risking price stability).